2008
DOI: 10.1258/cr.2008.080081
|View full text |Cite
|
Sign up to set email alerts
|

Labour ward incidents and potential claims – lessons learned from research

Abstract: This paper provides an insight into the underlying factors involved in potential cerebral palsy and/or shoulder dystocia claims. The research was undertaken to identify the root causes of 37 cases of birth asphyxia in term infants severe enough to warrant admission to neonatal care units in the north-west of England between 2001 and 2002. All available staff (n ¼ 93) providing care during critical periods were interviewed by the author using the cognitive interviewing technique. These included 81 midwives, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…A study by Ashcroft 13 highlighted the issues predisposing to negligent cases of SD currently in the UK. Mismanaged SD cases were found to be directly linked to system failures including allowing unsupported staff to work in a position for which they lacked sufficient skills, training knowledge or experience.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ashcroft 13 highlighted the issues predisposing to negligent cases of SD currently in the UK. Mismanaged SD cases were found to be directly linked to system failures including allowing unsupported staff to work in a position for which they lacked sufficient skills, training knowledge or experience.…”
Section: Discussionmentioning
confidence: 99%
“…They identified that in 78% of the cases, senior clinicians did not provide assistance to inexperienced clinicians (including junior paediatricians), and that the juniors often felt unable to ask for help for fear of being labelled as 'unable to cope'. 17 Issues relating to suboptimal communication were highlighted as a significant category of complaints, as noted above and in tables 1 and 2. However, we could also consider poor communication as contributary to errors resulting in malpractice claims.…”
Section: Category Of Complaintsmentioning
confidence: 97%
“…11 18 19 21 Factors implicated Some of the studies included did investigate contributing factors to errors resulting in complaints (see table 3). Ashcroft 17 undertook a cognitive interview of clinicians, exploring various factors implicated in serious incidents and outstanding claims on the Labour ward. This paper Open access that failing to take action, making the wrong decision or a delayed decision were implicated as human errors in all the cases of malpractice they presented.…”
Section: Category Of Complaintsmentioning
confidence: 99%
“…Not only are actual staffing levels important but so also are the ranges of expertise within the workforce across a 24‐hour period, with out‐of‐hour periods creating particular safety issues . This problem was exacerbated by the customary practice of using unsupervised junior medical staff in a first on‐call position for complications . With respect to task shifting, some evidence has been reported of improved outcomes and cost savings when midwives take on tasks previously within the remit of obstetric staff, for example, examination of the healthy newborn, which is usually carried out by junior doctors , and the role of advanced neonatal practitioners .…”
Section: Maternity Workforce Organization Staffing and Skill MIXmentioning
confidence: 99%